Bahasa Inggris - Wildi Adila; Djatmika N; Muhammad Rizal (Balai Bahasa Provinsi Riau, 2024)
The present study aimed to analyze how violations of maxim were used to create jokes. Grice’s notion of violation of maxims was used to analyze typical violation involved in jokes. The data in this study were in the form of texts comprising jokes. The data source was from compilation of jokes in Thomas Wilson Cathcart and Daniel Martin Klein’s Plato and A Platypus Walk into A Bar... book. The researchers applied a document analysis as a technique to collect the data. Meanwhile, in order to achieve validity of the data, the study used triangulation of data sources by providing varied data sources to achieve the complexity of the research objectives. Finally, to analyze the data, the present study employed Miles and Huberman’s formulation consisting of data reduction, data display, conclusion drawing and verification. The study found twenty-five data of jokes involving the use of violations as techniques to create humor. All data were classified into violations of language and culture and none categorized as cognitive violation. The jokes in this book were presented through three stages, namely premise, setup, and punchline. The violations here were employed in the punchline to create plot twist and humorous situation. These findings could serve as a foundation for future studies, particularly regarding jokes resulted from maxim violations in other genres such as a stand-up comedy, podcast, sitcom, or product review.